Towards band structure and band offset engineering of monolayer Mo(1−x)W(x)S2 via Strain. (16th October 2017) - Kim, Joon-Seok; Ahmad, Rafia; Pandey, Tribhuwan; Rai, Amritesh; Feng, Simin; Yang, Jing; Lin, Zhong; Terrones, Mauricio; Banerjee, Sanjay K; Singh, Abhishek K; Akinwande, Deji; Lin, Jung-Fu
Abstract: Semiconducting transition metal dichalcogenides (TMDs) demonstrate a wide range of optoelectronic properties due to their diverse elemental compositions, and are promising candidates for next-generation optoelectronics and energy harvesting devices. However, effective band offset engineering is required to implement practical structures with desirable functionalities. Here, we explore the pressure-induced band structure evolution of monolayer WS2 and Mo0.5 W0.5 S2 using hydrostatic compressive strain applied in a diamond anvil cell (DAC) apparatus and theoretical calculations, in order to study the modulation of band structure and explore the possibility of band alignment engineering through different compositions. Higher W composition in Mo(1− x ) W( x ) S2 contributes to a greater pressure-sensitivity of direct band gap opening, with a maximum value of 54 meV GPa −1 in WS2 . Interestingly, while the conduction band minima (CBMs) remains largely unchanged after the rapid gap increase, valence band maxima (VBMs) significantly rise above the initial values. It is suggested that the pressure- and composition-engineering could introduce a wide variety of band alignments including type I, type II, and type III heterojunctions, and allow to construct precise structures with desirable functionalities. No structural transition is observed during the pressure experiments, implying the pressure could provide selective modulation of band offset.